Geochronology and geochemistry of granodiorite at Jinwozi Au deposit: Tectonomagmatic evolution for Palaeozoic Beishan Orogen (Central Asian Orogenic Belt) in NW China. (19th April 2020) - Yu, Lidong; Zhang, Jing; Wang, Qisong; Wang, Chuanyi; Lai, Chunkit
Abstract : The Beishan Orogen (southern Central Asian Orogenic Belt) contains many Palaeozoic gold ore‐hosting intrusions, whose age, petrogenesis and tectonic setting are yet to be well understood. In the Mazongshan arc of the Beishan Orogen, the Jinwozi granodiorite contains high K2 O (2.71–5.69 wt%), A/CNK (1.10–1.49) and 10000Ga/Al (mostly >2.6), and has high Nb (15–21 ppm), Zr (337–451 ppm) and light rare earth element contents (∑LREE = 207–257 ppm), but low Sr (92–208 ppm) and negative Eu anomalies (δEu = 0.55–0.70), with calculated Zr saturation temperature of 910–860°C. They exhibit typical features of peraluminous A‐type granites formed in subduction‐related settings. The rocks have high large‐ion lithophile element and Hf contents, but low contents in certain high‐field‐strength elements. In addition, the zircon ε Hf ( t ) values (−3.6 to −0.1) indicate partial melting of the crust, while the two‐stage model ages ( T DM2 = 1385 to 1611 Ma) and several Palaeozoic magmatic rocks with Mesoproterozoic‐inherited zircon suggest the occurrence of Mesoproterozoic crustal accretion. The ore‐hosting granodiorite pluton at the Jinwozi Au deposit was LA‐ICP‐MS zircon U–Pb dated to be Silurian (ca. 428–422 Ma), older than the previously suggested Late Palaeozoic ages and before the interpreted amalgamation timing of the Beishan Orogen. We propose that the Jinwozi granodiorite is derived from pre‐existing crustal material recycling.